Efficacy of panchakarma based ischemia reversal therapy along with diet modification in management of ischemic heart disease - More-Mhaisane, Shital; Khan, Sadik; Patil, Sachin (International Journal of Basic & Clinical Pharmacology, 2024)
Background: Aim was to evaluate the efficacy of panchakarma-based ischemia reversal therapy combined with diet modification in the management of ischemic heart disease. Methods: A retrospective, single centre study was conducted at a Madhavbaug clinic in Maharashtra from February 2022 to December 2023. Patients aged 20-75 years diagnosed with ischemic heart disease were included in the study. Follow-up was conducted weekly, for total duration of 90 days. Day 1 and day 90 data were compared Results: A total of 22 patients with mean age of 58.64±9.81 years were included in this study. VO2max (day 1: 16.34±5.35 mL/kg/min and day 90: 28.11±7.39 mL/kg/min, p=0.00), duke treadmill score (day 1: -6.77±4.38 and day 90: 3.77±15.83, p=0.00), and MET value (day 1: 4.66±1.53 and day 90: 8.02±2.10, p=0.00) improved significantly at the 90-day follow-up. Conclusions: Ischemia reversal therapy has proven to be effective in improving the cardiac capacity of heart, demonstrated by improvement in VO2max. Also improved Duke’s treadmill score.